A new Neotropical emerald moth genus based on some unusual “artefacts” (Lepidoptera: Geometridae, Geometrinae) - Viidalepp, Jaan; Lindt, Aare (Zootaxa, 2019)
We describe a nemoriine emerald moth genus, Vallichlora gen. nov., with modified male genitalia, including two new species: Vallichlora rara sp. n.—the type species—and Vallichlora selva, sp. n. The genus is characterised by the presence of two long, thumb-shaped processes of the tegumen.